Duration of Freezing Influences Sensory Attributes of Cassava (Manihot esculenta Crantz) and Plantain (Musa paradisiaca AAB) - E. G, Mbassi Josiane; D, Mapiemfu-Lamare; Eliane F, Eyenga; A. F, Ngome (Journal of Food Technology Research, 2018)
In order to reduce post-harvest losses, this work was designed to evaluate the impact of freezing time on the organoleptic and nutritional properties of cassava and green plantain. Peeled fresh cassava (C), fresh plantain without peeling (PWP) and fresh plantain with peeling (PP) were cut into pieces of regular sizes, weighed, bagged in plastic packages and placed in a freezer at -18 °C. Over a period of 30 days, samples were removed from the freezer for sensory and nutritional analysis. Sensory analysis revealed that there was a significant difference (P≤0.05) between samples frozen at different time for different sensory attributes. The score for taste decreased from 3.56 to 2.9 for the cassava and 4.55 to 2.60 for the plantain with the increase in the time of freezing. As far as the overall acceptability is concerned, all the cassava samples were rated approximately the same, while for the plantain, there is significant difference between non-frozen and 30 days frozen. In fact, the score for the overall acceptability of non-frozen plantain was the highest (4.00) followed by 3 and 7 days frozen plantain and from 14 days of freezing, the samples had the least mean value (1.85) because they started getting brown and their taste has changed. Regarding the nutritional properties, there is no significant differences both for the cassava and plantain. Freezing time has no significant impact on the cassava while the taste and color of plantain change from the seventh day. Freezing time decrease the organoleptic properties of cassava and plantain but does not affect their nutritional quality.